Eleitoralismo e oligarquização da democracia : reflexões sobre o uso do sorteio como garantia do ideal republicano da não-dominação - Sousa, Rodrigo Ribeiro de, 1978 (2021)
Abstract: In recent years, the "malaise" of the world population with the rules and results of representative democracy has become a public and notorious fact in most democracies in the world. The corruption of the political system, the difficulties in overcoming social inequalities and the inability to include minorities reflect a persistent dominance of political elites, incompatible with civic-democratic values. Based on the observation of the practical limits of contemporary representative governments, in general, and of Brazilian representative democracy, in particular, the purpose of the article is to debate to what extent the reintroduction of the lot in our political practices may contribute to a rehabilitation of democratic values, promote social inclusion and favor the implementation of freedom as non-domination, in terms of the formulation of Philip Pettit. To achieve this purpose, recent theoretical references in the field of the so called "democratic nnovations" will be addressed, in particular the perspective of "open democracy", by Hélène Landemore. The methodology adopted is bibliographic analysis